Implications of an increase in domestic prices of gas in Russia, an application of the regional economic model SUSTRUS - Christophe Heyndrickx; Victoria Alexeeva-Talebi; Natalia Tourdyeva (European Regional Science Association (ERSA), 2012)
The present paper studies the effect of an upward correction of the natural gas price on the Russian domestic market. Russia has the largest gas reserves in the world and currently produces around 550 billion cubic meters of gas each year. Sixty percent of the production is sold domestically at prices below long term marginal cost, for households and for industrial producers. The pricing of natural gas is currently a hot topic in Russia, as the Russian government proposes to liberalize the regulated domestic market price and decrease subsidies for natural gas products. This is claimed to fit in a policy promoting energy efficiency, increasing investments in natural gas production and bringing the natural gas price on the domestic market closer to long term cost recovery. We will approach the issue of gas pricing through taxation of intermediate and final use of natural gas for domestic industries and consumers. Considerable attention is given to economic impacts, environmental issues and social effects of gas pricing. We compare several scenarios of differential gas pricing, simulating increases in price for industrial and private consumers at different annual growth rates, with a time horizon from 2012 until 2020. Our results are based on an application of the SUSTRUS model, a novel computable general equilibrium model, which was developed in the same-named EU funded project. The SUSTRUS model belongs to the group of regional CGE models, applied to analyze policies with a strong social, economic and environmental dimension. The model is constructed as a regional model on federal level, where regions are linked by interregional trade flows, a federal government level and migration. The main data sources for the model are the public databases of Rosstat and the micro-level household data from the Russia Longitudinal Monitoring Survey (RLMS). Calibration of the model database was performed by a flexible cross-entropy minimization sub module and standard applied general equilibrium techniques. We find that deregulating natural gas pricing can lead to a significant improvement in energy efficiency, if prices are gradually increased for both consumers and industries alike. Differences in regional energy efficiency decrease, but are still significant. We show that increasing the consumer price of gas is indeed a regressive policy, but can be compensated for by the government.
Keywords: R13; Q01; Q41; Q48; Q56; 330; Regional general equilibrium modeling; sustainability; energy; natural gas; pricing; policy